Work-related coping behaviour and experience patterns in university students: a review of 20 years of research - Mašková, Ivana (Frontiers in Psychology, 2023)
Work-related coping behaviour and experience patterns (WCEP) is the conceptualisation of personal experience with occupational stress and of the typical behavioural responses for coping with such stress. The objective of this review, which is based on 69 references that used the WCEP inventory in university students, is to summarise the most important findings on WCEP and their correlates in the student population. The results of the published studies consistently show that female students, teacher education students (compared to medical students), and students who receive insufficient social and financial support are at greater risk for being assigned to work-related patterns that indicate vulnerability to burnout and occupational health issues. Moreover, students assigned to these patterns, especially to the resigned (burnout) pattern, are prone to manifest other negative characteristics, such as less adaptive personality traits and coping strategies, vulnerability to stress, lower quality motivation, lack of commitment to the chosen career and suitability for the profession, and impaired physical and mental health. In contrast, the most desirable correlates, such as adaptive personality traits, higher quality motivation, commitment to the chosen career, suitability for the profession, stress resistance, adaptive coping, and better physical and mental health, were related to the healthy ambitious pattern. Nevertheless, further research is needed to analyse work-related coping behaviour and experience patterns beyond the German speaking population to increase the generalisability of the findings.